2015
DOI: 10.1016/j.watres.2015.05.052
|View full text |Cite
|
Sign up to set email alerts
|

Cerium incorporated MCM-48 (Ce-MCM-48) as a catalyst to inhibit bromate formation during ozonation of bromide-containing water: Efficacy and mechanism

Abstract: a b s t r a c tThe composite mesoporous sieve Ce-MCM-48 (cerium incorporated MCM-48) with different Si/Ce molar ratios were synthesized hydrothermally and characterized with X-ray diffraction, X-ray photoelectron spectroscopy, BET surface area, and pH pzc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Li et al [19] studies confirmed that bromate formation increased significantly in ozonation alone as pH was increased from 6.3 to 9.5. This can be due to fact that in alkaline medium (i) OH shifts the acid/base equilibria of HOBr false(pKa= 8.8) towards OBr, which reacts readily with both O3 and HO [1], and (ii) OH decomposes O3 to HO radicals, which enhances BrO3 formation.…”
Section: Factors Affecting Bromate Minimizationmentioning
confidence: 96%
See 4 more Smart Citations
“…Li et al [19] studies confirmed that bromate formation increased significantly in ozonation alone as pH was increased from 6.3 to 9.5. This can be due to fact that in alkaline medium (i) OH shifts the acid/base equilibria of HOBr false(pKa= 8.8) towards OBr, which reacts readily with both O3 and HO [1], and (ii) OH decomposes O3 to HO radicals, which enhances BrO3 formation.…”
Section: Factors Affecting Bromate Minimizationmentioning
confidence: 96%
“…Li et al [19] reported on catalytic ozonation of bromide containing waters with MCM-48, CeO 2 and combined mesoporous sieve Ce x -MCM-48 (cerium combined with MCM-48) with various Si/Ce molar ratios (Ce 30/66/100/200 -MCM-48). All catalysts were able to considerably impede BrO3 formation in comparison to ozonation alone.…”
Section: Bromate Minimization Strategiesmentioning
confidence: 99%
See 3 more Smart Citations